2001
DOI: 10.1002/1099-0682(200112)2001:12<3119::aid-ejic3119>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure and Physical Properties of Tetrabutylammonium Salts of Nickel Complexes with the New Ligand dcbdt = 4,5-dicyanobenzene-1,2-dithiolate, [Ni(dcbdt)2]z− (z = 0.4, 1, 2)

Abstract: The synthesis and characterization of the new aromatic ortho-dithiol, 4,5-dicyanobenzene-1,2-dithiol (3) is reported. This compound was used to prepare tetrabutylammonium salts of novel nickel complexes; the nickel(II) salt (nBu 4 N) 2 -[Ni(dcbdt) 2 ] (4), the nickel(III) salt (nBu 4 N) 2 [Ni(dcbdt) 2 ] 2 (5), and the partially oxidized Ni III/IV salt (nBu 4 N) 2 [Ni(dcbdt) 2 ] 5 (6). (dcbdt = 4,5-dicyanobenzene-1,2-dithiolate). The Ni II complex presents a square-planar coordination geometry and is diamagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 39 publications
(28 reference statements)
1
15
1
Order By: Relevance
“…All solvents and reagents were of the highest qualities available and were used as received without further purification. 4,5‐Dicyanobenzene‐1,2‐dithiol (dcbdtH 2 ), ( n ‐Bu 4 N) 2 [Ni II (dcbdt) 2 ], and Ni II (bpy)(qdt) (qdt=quinoxaline‐2,3‐dithiolate) were synthesized as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…All solvents and reagents were of the highest qualities available and were used as received without further purification. 4,5‐Dicyanobenzene‐1,2‐dithiol (dcbdtH 2 ), ( n ‐Bu 4 N) 2 [Ni II (dcbdt) 2 ], and Ni II (bpy)(qdt) (qdt=quinoxaline‐2,3‐dithiolate) were synthesized as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Cp*H (1,2,3,4,5-pentamethylcyclopentadiene), 4,5-dichlorophthalonitrile, and 5,6-dichloropyrazine-2,3-dicarbonitrile were obtained from Wako Pure Chemicals Industries, Ltd. RhCl 3 Á3H 2 O and IrCl 3 ÁnH 2 O were obtained from STREM Chemicals. [Cp*Co(-CO) 2 ] [41], [Cp*Co(CO)I 2 ] [42], [Cp*M(Cl)(l-Cl)] 2 (M = Rh, Ir) [29], (PhCH 2 ) 2 (dcbdt) (1) [24], and (PhCH 2 ) 2 (dcdmp) (2) [43] were prepared by literature methods. Mass and IR spectra were recorded on a JEOL JMS-D300 and a Shimadzu Model FTIR 8600PC instruments, respectively.…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…However, there is a synthetic difficulty using the precursor [Cp* 2 Ni]. Almeida et al have reported a rich family of square-planar or tetrahedral bisdithiolene complexes (M = Fe, Co, Ni, Pd, Pt, Cu, Au and Zn) based on the dcbdt [23,24] and the dcdmp ligands [25,26] and their structural, magnetic and electrical conductive properties have been studied as well [23][24][25][26]. Furthermore, Ueda et al have reported the oxo-vanadium bisdithiolene complex of the dcbdt, [O@V(dcbdt) 2 ] [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations